2015
DOI: 10.4103/0973-6247.154251
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid reduces blood loss and need of blood transfusion in total knee arthroplasty: A prospective, randomized, double-blind study in Indian population

Abstract: Introduction:For quite a few years, tranexamic acid (TEA) has been used during total knee arthroplasty (TKA) to reduce blood loss. However, no consensus exits regarding its timing and doses.Materials and Methods:We conducted a prospective, randomized double-blinded study of 56 patients in the Indian population undergoing TKA from 2011 to 2012. A dose of 10 mg/kg body weight of TEA (three doses) was given in one group and normal saline was administered in the other.Results:The mean blood loss in the TEA unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The electronic database and manual search yielded a total of 782 studies published between 1976 and 2018. In total, 381 articles were considered for full-text review, of which 189 were excluded because of ineligible study designs (n = 55) or control groups (n = 92), ineligible end points (n = 27), missing or nontranslatable full text (n = 11), and duplicates (n = 4), leaving 192 RCTs for final analysis (Figure). Included studies were published in English, German, French, and Spanish.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic database and manual search yielded a total of 782 studies published between 1976 and 2018. In total, 381 articles were considered for full-text review, of which 189 were excluded because of ineligible study designs (n = 55) or control groups (n = 92), ineligible end points (n = 27), missing or nontranslatable full text (n = 11), and duplicates (n = 4), leaving 192 RCTs for final analysis (Figure). Included studies were published in English, German, French, and Spanish.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 9,067 patients received TXA while 6,592 were included in the control groups. With regard to the type of surgery, 82 studies [ 21 24 , 26 28 , 30 , 31 , 34 38 , 40 , 45 , 47 , 49 51 , 55 58 , 60 , 61 , 63 , 65 , 66 , 70 , 72 , 73 , 75 , 76 , 78 – 82 , 84 , 85 , 87 , 88 , 90 , 92 , 93 , 96 , 98 , 99 , 104 111 , 113 , 114 , 117 119 , 121 , 123 , 124 , 126 – 128 , 130 , 134 137 , 140 142 , 146 , 147 , 151 , 153 , 154 , 156 ] (5,267 cases and 3,498 controls) were focused on TKA, 41 studies [ 11 , 12 , 25 , 32 , 33 , 42 44 , 48 , 52 54 , 62 , 64 , 67 …”
Section: Resultsmentioning
confidence: 99%
“…Multimodal blood management protocols included drain clamping for 4 h and the use of tranexamic acid both in the LIA and intravenously. 10,23 We were able to keep the number of blood transfusions down to 0.51% patients in the UTKA group and 3.94% patients in the BTKA group. Morais et al reported no transfusions using a multimodal blood loss prevention approach in their study.…”
Section: Discussionmentioning
confidence: 90%